Geochemical Association of Ni2+, Zn2+, Pb2+, Ag+, Cu2+, and Co2+ Ions in Natural Pyrite. (7th May 2014) - Baruah, Mrinal K.; Kotoky, Probhat; Borah, Gobin C.
Abstract : The natures of competitive adsorption of six metal ions on the natural pyrite surface have been studied with an objective to provide strong foundations towards mode of association/occurrence of trace elements on pyritic surface. Some parameters, for instance, adsorption edge, mechanism, correlation coefficient, monolayer coverage, pH, and thermodynamic parameters, have been considered here. The significant results are the order of increasing trend of adsorption edges which has been found to be Pb 2+ < Cu 2+ < Ni 2+ < Zn 2+ < Co 2+ < Ag + . Nonuniformity in variation of adsorption edge of a particular metal ion in presence of a second metal ion in solution is evident from the study. However, in case of Ag 2+ and Co 2+ ions two adsorption edges are observed. These variations have been explained based on the formation of hydroxo complexes which are pH dependent. The competitive monolayer coverage of each metal ion as a function of pH has shown variation in the extent of adsorption. Computed higher correlation coefficient in a binary system indicates retardation in adsorption of metal ion in presence of a second metal ion. Further the adsorption of metal ions on pyrite surface showed exothermic processes due to the spontaneous nature at low temperature. Our study has strongly revealed promising adsorbent characteristics of natural pyrite with considerable geochemical and environmental implications.